Table of Content - -, (Journal of Educational and Psychological Sciences, 2025)
Table of Content:1. The Role of female principals of school in Enhancing Information Security at the Secondary Level  in Al-Kharj GovernorateMs. Suha Fahad Al-Mosa2. Proposed Research priorities for Doctoral dissertations in educational administration  at Taibah University and the Islamic University in Al-MadinahMs. Maha Saleh Saad Alyahyan , Ms. Wafiah Othman Alsubhi ,Co-Prof. Norah Mohamed Aljumah3. Employing modern technology to support the teaching and learning process in primary schools  in Al-Dakhiliyah Governorate in the Sultanate of OmanDr. Ali Saif Al-Durai4. Psychological stress and its relationship life Satisfaction among a sample of male and female students at Taif UniversityMs. Amjad Ahmed Alzahrani ,Dr. Suha Omar Alharthi5. The Effect of the Parental Treatment Style of the Firm Mother on Social Adjustment in University Life Among Students of Sultan Qaboos University in the Sultanate of OmanMs. Farida Said Sulaiman Alsharji,Co-Prof. Norwati Mansour6. Relationship of Bullying with psychological security and Self-Esteem among a sample of first year students at Tabuk University in TabukMs. Joud Masad Alodhayyani, Dr. Ahmed Ali Alhomidi7. Evaluating the Implementation of the Training Needs Assessment Policy at Imam Muhammad  ibn Saud Islamic UniversityDr. Dalia Abdulaziz Alharbi, Dr. Alaa Ibrahim Alhijji, Dr. Manal Trekhem Alharthi ,  Co-Prof. AlJawhrah Othman Ali AlRakban
Keywords: Journal of Educational and Psychological Sciences